Young adult consumers' involvement in branded smartphone based service apps: Investigating the roles of relevant moderators. Issue 6 (2nd December 2019) - Sarkar, Juhi Gahlot; Sarkar, Abhigyan
Abstract : Purpose: The purpose of this paper is to investigate various factors that shape young adult consumers' smartphone-based service app involvement and their subsequent development of brand loyalty for the app. Design/methodology/approach: A survey was conducted to test the hypothesized relationships. The survey data were analyzed using SPSS-based PROCESS macro (Hayes, 2013 ). Findings: The study results show that consumer can perceive an app to be largely hedonic or utilitarian, and the perceived app design (hedonic vs utilitarian) impacts consumers' involvement with a particular service app category. Further, the findings elucidate that the impact of app hedonism on app category involvement is moderated by consumer's surfing task orientation and the extent to which app arouses their imagination. On the other hand, the impact of app utilitarianism on app involvement is moderated by consumer's information-seeking task orientation and perceived relevance of the information. Finally, app category involvement predicts loyalty toward a particular brand in the service app category. The effect of app involvement on brand loyalty is moderated by hot and cold brand relationship quality in cases of hedonic and utilitarian apps, respectively. Originality/value: The value of this research lies in identifying relevant managerially actionable moderators that shape the relationships between perceived dominant app design (hedonic vs utilitarian), app category involvement and app brand loyalty.